Seraphina - Hartman, Rachel 1972- (New York Ember, 2013)
Four decades of peace have done little to ease the mistrust between humans and dragons in the kingdom of Goredd. Seraphina Dombegh has reason to fear both sides. An unusually gifted musician, she joins the court just as a member of the royal family is murderedNin suspiciously draconian fashion.
Includes bonus material: A Q & A with Rachel Hartman; Rachel Hartman's favorite authors; "The Audition," a prequel short story (p. [467]-499)
Keywords: Self-actualization (Psychology) -- Juvenile fiction; Dragons -- Juvenile fiction; Trade secrets -- Juvenile fiction